The Effectiveness of Mobile Health Utilization to Prevent Non-Communicable Diseases at the Group of Majlis Taklim - Leonita, Emy; Hastuti Marlina; Nopriadi (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Mobile health application is a technological innovation that has proven effective use for the prevention and management of NCDs in other countries. However, there has been no test on the use of mobile health applications that have been launched in Indonesia, including the Halodoc application. The majlis taklim group is a target group in increasing community empowerment in the family order. Aims: This study was to examine Halodoc application in preventing noncommunicable diseases. Methods: The population is the member of the majlis taklim who was active in the last three months. The sample was respondents who were identified as having knowledge and bad behavior in NCD prevention efforts, 45 people. Descriptive analysis on respondents' characteristics and level of knowledge. While analytical analysis consists of dependent T tests to determine the difference in effectiveness before and after utilizing the application, the next test is the CBAM-Stage of Concern test, which is to assess respondents' perceptions through the level of respondents' concern for halodoc innovation. Results: Univariate analysis found that most respondents were poorly educated, namely 35 respondents (78%), as IRT 30 respondents (67%), family history of NCD disease 30 respondents (67%), and history of NCD disease in themselves 10 respondents (22%). The level of knowledge on the pretest was low at 23 respondents (51%), and the knowledge on the posttest was mostly high at 31 respondents (69%). Conclusion: The result of the dependent T test obtained a value of 0.000 means that statistically there is a significant difference in knowledge before and after the use of Halodoc for the prevention and management of NCDs. The test results with the Stage of Use Consern Questionnaire (SoC) analysis, obtained information on the percentage of respondents' perception of the highest acceptance of innovation before being given the Halodoc intervention (pretest) at the personal level, which is 60%. However, after utilizing Halodoc, most respondents' perceptions were at the level of unconcern, which was 81%.